2021
DOI: 10.1111/ans.16640
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of burn scar contracture deformity of the extremities using thin thoracodorsal artery perforator free flaps

Abstract: Background: Severe burn scar contracture of the extremities, especially the joint areas, causes aesthetic problems and functional limitation. Release of burn scar contractures requires complete removal of the scars and resurfacing of the resulting defects. Here, we describe thoracodorsal artery perforator (TDAP) free flaps for reconstructing burn scar contractures. Methods: Between August 2013 and July 2018, 25 patients with severe burn scar contractures of the extremities underwent reconstruction using TDAP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Woerd et al reported that sialocutaneous fistula to the external auditory canal was covered with a temporal fascia flap after the excision of salivary glands 11) , where the efficacy of the transplanted free groin flap was maximized for multiple reconstructive objectives, with free flaps being functionally and cosmetically superior in surgery for burn scar contractures 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Woerd et al reported that sialocutaneous fistula to the external auditory canal was covered with a temporal fascia flap after the excision of salivary glands 11) , where the efficacy of the transplanted free groin flap was maximized for multiple reconstructive objectives, with free flaps being functionally and cosmetically superior in surgery for burn scar contractures 12) .…”
Section: Discussionmentioning
confidence: 99%
“…However, novel techniques of reducing FTSGs contraction using dermal substitutes are promising [17]. On the other hand, when a wide area is involved in contracture, it is difficult to reconstruct the neck using conventional methods because skin grafting often results in postoperative re-contracture, and the amount of uninvolved skin available for use as a local flap is usually insufficient [18].…”
Section: Discussionmentioning
confidence: 99%
“…Complete flap elevation with preservation of the perforator and intermuscular septum is created and the flap was rotated in the defect Fig. (4).…”
Section: Posterior Interosseous Artery Perforator Flapmentioning
confidence: 99%
“…Reconstruction of complex wounds of the upper limb is a challenge for the plastic surgeon. Machi-21 nary injuries [1], road traffic accidents [2], tumor ablation [3] and burn scars reconstruction [4] are the main causes of complex wounds in the upper extremity. These wounds entails exposure of tendons, bones, nerves or blood vessls and they need flap coverage [5].…”
Section: Introductionmentioning
confidence: 99%